Remote sensing for monitoring rangeland condition: Current status and development of methods - Angus Retallack; Graeme Finlayson; Bertram Ostendorf; Kenneth Clarke; Megan Lewis (Environmental and Sustainability Indicators, 2023)
This paper reviews the current status and development of remote sensing methods for monitoring rangeland condition. Remote sensing offers ideal solutions for assessing ecological indicators in vast and remote rangeland regions, with expanding opportunities emerging through new platforms, sensors and analytical methods. We summarise indicators widely used to assess rangeland ecosystem structure, function, and composition and review remote sensing methods for measuring them. We present a framework for rating the maturity of these methods and evaluate their potential for implementation into operational monitoring programmes.There is a distinct lack of uptake of remote sensing methods beyond regional-scale satellite products, with on-ground approaches remaining dominant for many essential indicators. However, we highlight considerable recent research using rapidly developing sensor and platform technologies, such as LiDAR and UAVs, which provide unprecedented types and resolutions of data and are driving development of information extraction methods. Three-dimensional modelling using structure from motion (SfM) and LiDAR is increasingly used for measuring all aspects of ecosystem condition and may also improve assessment of ecological indicators where spectral sensing has reached its limit.We introduce a framework for assessing remote sensing capabilities and maturity, and provide an overview of development pathways, which will focus ongoing research and development. It may also stimulate uptake of well-developed remote sensing methodologies into operational monitoring programmes by land managers. The use of best-available methods will greatly assist in maintaining and improving the condition of global arid ecosystems, benefiting all stakeholders in these regions, and preserving their natural services for future generations.